Social representation of young adults about COVID-19 vaccination - Barbosa, Ana Clara Rodrigues; Souza, Marilza Alves de; Dias, Otávio Leone Machado Teixeira; Rocha, Jucimere Fagundes Durães; Franco, Cintya dos Santos; Santos, Merilaine Isabel dos; Dias, Natália Cristina de Andrade; Bastos, Lícia Caroline; Martins, Priscila Oliveira (Seven Editora, 2023)
Objective: to analyze the relationship of prediction and social representations of young adults about vaccination against Covid-19. Materials and Methods: this is an exploratory and descriptive field research, with a qualitative approach, based on the Theory of Social Representations. The present study was carried out in Montes Claros and Curral de Dentro, where data were collected through a semi-structured questionnaire, with the aim of evaluating the social representation of the Covid-19 vaccine. Data were tabulated and organized in the Satistical Package for the Social Science Program and analyzed using the Ensemble de Programs Permettant l’Analyse des Evocations software. Results: the relationship of the social representation of adults about vaccination against Covid-19 showed the formation of two large groups, namely, the first group: immunization-immunity, health, protection-prevention, science and SUS; and the second group: hope, freedom, healing and lifesaving. Conclusion: it is concluded that there are relationships between social representations and prediction for vaccination against Covid-19. The analysis of individual and collective experiences revealed that the intention to vaccinate is not only related to the prior knowledge that the population has about the vaccine, but also to the feeling that this brings to society. DOI:https://doi.org/10.56238/sevened2023.006-095